Microplastic contamination in soil agro-ecosystems: A review - Jean Yves Uwamungu; Yibo Wang; Guoxi Shi; Sujuan Pan; Zhibo Wang; Lisha Wang; Shuzhen Yang (Environmental Advances, 2022)
Microplastics (MPs) have been a significant worldwide issue, becoming persistent and emerging contaminants in the environment. While MPs have been the subject of extensive scrutiny in the aquatic environment, their presence, mobility, and potential for pollution control, notably in African, Latin American, Oceanian, and some Asian agro-ecosystems, remain unknown. Most MPs in croplands come from composite pesticides and fertilizers, organic waste and compost, mulch films, wastewater irrigation, and atmospheric deposition. MPs' ultimate mobility and fate in the soil ecosystem are driven mostly by MPs' physicochemical properties, soil properties, farming techniques, and soil biota heterogeneity. In different global agro-ecosystems, this review explores the MPs' origins, mobility, fate, and pollution control in the soil agro-ecosystems and explores MPs' contaminant-transport capacity and toxicity impact on soil organisms. Future studies should focus on deleterious implications on animals and humans, irregular mobility and behavior in the soil agro-ecosystems, optimum management techniques, and worldwide agricultural policies to promote sustainable development.